Jerzy Rzedowski Rotter (1926-2023) - Medina Lemos, Rosalinda; Grether, Rosaura (Instituto de Ecología, A.C., 2023)
This profile does not pretend to be exhaustive, its purpose is to highlight the importance of an exceptional academic life.